Molecular beam epitaxy of InAs nanowires in SiO2 nanotube templates: challenges and prospects for integration of III–Vs on Si. (3rd October 2016) - Vukajlovic-Plestina, Jelena; Dubrovskii, Vladimir G; Tütüncuoǧlu, Gözde; Potts, Heidi; Ricca, Ruben; Meyer, Frank; Matteini, Federico; Leran, Jean-Baptiste; i Morral, Anna Fontcuberta
Abstract: Guided growth of semiconductor nanowires in nanotube templates has been considered as a potential platform for reproducible integration of III–Vs on silicon or other mismatched substrates. Herein, we report on the challenges and prospects of molecular beam epitaxy of InAs nanowires in SiO2 /Si nanotube templates. We show how and under which conditions the nanowire growth is initiated by In-assisted vapor–liquid–solid growth enabled by the local conditions inside the nanotube template. The conditions for high yield of vertical nanowires are investigated in terms of the nanotube depth, diameter and V/III flux ratios. We present a model that further substantiates our findings. This work opens new perspectives for monolithic integration of III–Vs on the silicon platform enabling new applications in the electronics, optoelectronics and energy harvesting arena.